The Prevalence of Klebsiella spp. Associated With Bovine Mastitis in China and Its Antimicrobial Resistance Rate: A Meta-Analysis - Liu, Kai; Zhang, Limei; Gu, Xiaolong; Qu, Weijie (Frontiers in Veterinary Science, 2022)
abstract To contribute to the treatment decision and optimize Klebsiella spp. control programs, we conducted a meta-analysis to investigate the epidemiology and antimicrobial resistance rates of Klebsiella spp. associated with bovine mastitis in China. Three databases, namely, PubMed, Google scholar, and China National Knowledge Infrastructure database, were utilized to obtain relevant publications. A total of 38 publications were included in our research, and 7 of them included an AMR test. The pooled prevalence of Klebsiella spp. was 5.41% (95% confidence interval (CI): 3.87%–7.50%). Subgroup analysis revealed that the prevalence was higher in South China (8.55%, 95% CI: 3.57%–19.09%) than in North China (4.22%, 95% CI: 2.46%–7.14%), in 2010–2020 (7.45%, 95% CI: 5.29%110.40%) than in 2000–2010 (3.14%, 95% CI: 1.90%15.14%), and in clinical bovine mastitis cases (7.49%, 95% CI: 3.71%–14.54%) than in subclinical cases (4.03%, 95% CI: 1.55%–10.08%). The pooled AMR rate revealed that Klebsiella spp. were most resistant to sulfonamides (45.07%, 95% CI: 27.72%–63.71%), followed by tetracyclines (36.18%, 95% CI: 23.36%–51.34%), aminoglycosides (27.47%, 95% CI: 17.16%–40.92%), β-lactams (27.35%, 95% CI: 16.90%–41.05%), amphenicol (26.82%, 95% CI: 14.17%–44.87%), lincosamides (21.24%, 95% CI: 7.65%–46.75%), macrolides (20.98%, 95% CI: 7.20%–47.58%), polypeptides (15.51%, 95% CI: 6.46%–32.78%), and quinolones (7.8%, 95% CI: 3.25%–17.56%). The climate difference between South and North China and the natural pathogenicity of Klebsiella spp. may be the primary reasons for its distribution, and the increase in the prevalence Klebsiella spp. indicated that the genus is increasingly becoming hazard to the dairy industry. The prevalence of AMR in China is commonly higher than in European countries and Canada, which should rise the concern when take control programs of Klebsiella spp. in China.